-(-5-6q)=4(5q+3)

Simple and best practice solution for -(-5-6q)=4(5q+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-5-6q)=4(5q+3) equation:



-(-5-6q)=4(5q+3)
We move all terms to the left:
-(-5-6q)-(4(5q+3))=0
We add all the numbers together, and all the variables
-(-6q-5)-(4(5q+3))=0
We get rid of parentheses
6q-(4(5q+3))+5=0
We calculate terms in parentheses: -(4(5q+3)), so:
4(5q+3)
We multiply parentheses
20q+12
Back to the equation:
-(20q+12)
We get rid of parentheses
6q-20q-12+5=0
We add all the numbers together, and all the variables
-14q-7=0
We move all terms containing q to the left, all other terms to the right
-14q=7
q=7/-14
q=-1/2

See similar equations:

| 33=4a7 | | 8x+32=-2x+-18 | | -4(u+2)+2=(u+6) | | -16+10.2g=-14.7g+16.85 | | 3(2n+6)=5n+8-7+n | | 6-6s=72 | | -8=s/4=3 | | -x-6=-28 | | 28-4x=19 | | -1=b-2-2 | | 9x+4=x-(7-8x) | | 2b-5=b+2 | | 22y-2/3=2y=4/3 | | -2y=1-3y | | 16+3n=8+5(2n-4) | | 10.60=x2.95+1.75 | | 5x+8=0x+3 | | 5(4x+-12)=4x+4 | | 710+35x=570-25x | | 6x—7=5x-1 | | b+5/2=1 | | 5=4/3(6x+9) | | 2n-5n=36 | | -3/2x+2=2/3x-3 | | .10+1/3y=1 | | 2y-3+4=3y-5 | | 2x+3=x- | | r=6+1/3 | | -8q-5+3q=7+4q-9 | | ¾(x+8)=9 | | 5-4x=2x2+x;x=3 | | 12/5x=1/3 |

Equations solver categories